The Role of Self-Efficacy on Job Satisfaction through Work Engagement for Automotive Company Employees - Soemadi, Rd Roro Anggraini (IJOSMAS, 2022)
This study investigates whether and how job involvement mediates the relationship between self-efficacy and job satisfaction among 264 employees in an automotive company in Indonesia. Survey data were analyzed using partial least squares structural equation modeling (PLS-SEM). Supported by cognitive social self-efficacy theory and self-determination theory of job involvement, the results of this study indicate that employees' self-efficacy has a positive effect on their job satisfaction through mediating job involvement. The implications for a proper focus on increasing self-efficacy through coaching are discussed in this study.